NMR Metabolite Profiles of the Bivalve Mollusc Mytilus galloprovincialis Before and After Immune Stimulation With Vibrio splendidus - Frizzo, Riccardo; Bortoletto, Enrico; Riello, Tobia; Leanza, Luigi; Schievano, Elisabetta; Venier, Paola; Mammi, Stefano (Frontiers in Molecular Biosciences, 2021)
The hemolymph metabolome of Mytilus galloprovincialis injected with live Vibrio splendidus bacteria was analyzed by 1H-NMR spectrometry. Changes in spectral hemolymph profiles were detected already after mussel acclimation (3 days at 18 or 25 °C). A significant decrease of succinic acid was accompanied by an increase of most free amino acids, mytilitol and, to a smaller degree, osmolytes. These metabolic changes are consistent with effective osmoregulation and the restart of aerobic respiration after the functional anaerobiosis occurred during transport. The injection of Vibrio splendidus in mussels acclimated at 18°C caused a significant decrease of several amino acids, sugars and unassigned chemical species, more pronounced at 24 than at 12 hours post-injection. Correlation heatmaps indicated dynamic metabolic adjustments and the relevance of protein turnover in maintaining the homeostasis during the response to stressful stimuli. This study confirms NMR-based metabolomics as a feasible analytical approach complementary to other ‘omics techniques in the investigation of the functional mussel responses to environmental challenges.